Trauma and Mothering: An Autoethnography - Cauley, Noreen Anne (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
Sexual violence and mothering are prevalent events in women’s lives. However, they are not often studied together from a feminist perspective. This essay uses autoethnography to explore the parallels between sexual violence and mothering. Specifically, this essay examines the medical models of trauma and childbirth, Maushart’s “mask of motherhood,” rape myths, patriarchal mothering, and empowered mothering. I argue that more vigorous interrogations of the commonalities and differences of mothering and rape will open strategic avenues for female growth, learning, and empowerment.